Rationality and ethics in Franz Hinkelammert: Hinkelammert's critique of the orthodox theory of rational action - Mora Jiménez, Henry (2025)
The article develops the fundamental distinction that Franz Hinkelammert establishes between means-end instrumental rationality and reproductive rationality of life, and why the former (without denying its theoretical and practical status) should be subordinated to the latter. Three types of judgments are distinguished: means-end judgments, lifedeath judgments, and value judgments. Only if we discard life-death judgments (which are judgments of fact), value judgments turn out to be alien to scientific discussion, since these